ASEAN 4.0 what does the fourth industrial revolution mean for regional economic integration. (Metro Manila, Philippines Asian Development Bank, 2017)
The Fourth Industrial Revolution refers to a set of highly disruptive technologies, such as artificial intelligence (AI), robotics, blockchain and 3D printing, that are transforming social, economic and political systems and placing pressure on leaders and policy-makers to respond.The paper discusses the huge benefits these technologies will bring, such as empowering SMEs and creating new ways to connect citizens to healthcare. Equally, it will bring tremendous challenges, such as deep disruption to jobs as AI and advanced robotics undermine both manufacturing and services jobs. The region will need a new approach to policy and governance to help it navigate these technologies, which do not recognize national borders.This research report was suggested by the World Economic Forums ASEAN Regional Strategy Group. The report was written and researched jointly by the World Economic Forum and the Asian Development Bank (ADB).
Keywords: Information technology -- Developing countries; Electronic books